Dynamics of the compartmentalized Streptomyces chromosome during metabolic differentiation - Virginia S. Lioy (Nature Portfolio, 2021)
Streptomyces bacteria have a linear chromosome, with core genes located in the central region and gene clusters for specialized metabolite biosynthesis found in the ‘arms’. Here, Lioy et al. show that such chromosome structure correlates with genetic compartmentalization, and the onset of metabolic differentiation is accompanied by a rearrangement of chromosome architecture.